2016
DOI: 10.1038/nphoton.2016.129
|View full text |Cite
|
Sign up to set email alerts
|

Hologram of a single photon

Abstract: The complete characterization of a quantum wavefunction of an unknown photon presents a challenging task whose difficulty lies particularly in the retrieval of its local phase variations. This is caused by the fundamental property of single photons i. e. their entirely indeterminate global phase following from the perfect rotational symmetry of their Wigner functions in the phase space [14], which precludes the application of interferometric techniques such as optical holography utilizing fixed phase relation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
82
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(83 citation statements)
references
References 37 publications
1
82
0
Order By: Relevance
“…The authors had previously shown that the intensified CMOS camera they used was able to perform spatially resolved multiphoton counting [75]. This work led to subsequent demonstrations using a similar setup, such as the acquisition of holograms in a single photon regime [76], the demonstration of bi-photon mode engineering for quantum-enhanced interferometry [77], and the demonstration of a wave-vector multiplexed quantum memory for photons interacting with cold atoms [78].…”
Section: Intensified Camerasmentioning
confidence: 99%
“…The authors had previously shown that the intensified CMOS camera they used was able to perform spatially resolved multiphoton counting [75]. This work led to subsequent demonstrations using a similar setup, such as the acquisition of holograms in a single photon regime [76], the demonstration of bi-photon mode engineering for quantum-enhanced interferometry [77], and the demonstration of a wave-vector multiplexed quantum memory for photons interacting with cold atoms [78].…”
Section: Intensified Camerasmentioning
confidence: 99%
“…The first layer of the interferometer is realized by inserting two beam splitters (BS) on input modes 2 and 5. In this way the four-photon input is probabilistically split to six modes (1,2,3,4,5,6). Each BS of the first layer is realized with a half-wave plate and a PBS.…”
Section: Appendix B Experimental Implementationmentioning
confidence: 99%
“…Photon indistinguishability is a key concept in quantum physics, which can be characterized via two-particle interference [1]. From the first experimental observation carried out using entangled photons produced by a parametric down-conversion source [2], the quantum signature of this phenomenon, known as Hong-Ou-Mandel (HOM) effect, has proved to be essential for tasks such as characterization of single photon sources, practical protocols of quantum communication [3][4][5] and quantum computation. Recent proposals use twophoton interference for the realization of two-qubit gates, essential elements for photon-based quantum computing schemes [6].…”
Section: Introductionmentioning
confidence: 99%
“…Thankfully, recent advances of charge-coupled device (CCD) cameras make it possible to directly image spatial output results at a single-photon level [17][18][19][20][21][22][23][24]. HOM interference was also successfully verified by low-noise correlation detection on two modes with an intensified camera [25].…”
mentioning
confidence: 98%
“…In practice, it may still be acceptable to place single photon detector behind each spatial mode for comparably small systems [9, 14-16]. However, it will become both technically challenging and economically unfeasible to address thousands of modes simultaneously with single photon detectors, and therefore become a decisive bottleneck preventing from detecting state spaces large enough for real quantum applications.Thankfully, recent advances of charge-coupled device (CCD) cameras make it possible to directly image spatial output results at a single-photon level [17][18][19][20][21][22][23][24]. HOM interference was also successfully verified by low-noise correlation detection on two modes with an intensified camera [25].An alternative and elegant approach we present in this work is to convert the modes in different degrees of freedom into the modes in position, and then measure all the spatial modes accordingly by the large number of units in singlephoton-sensitive cameras.…”
mentioning
confidence: 99%